Cross-Cultural Adaptation and Preliminary Psychometric Evaluation of the Indonesian Antenatal Risk Questionnaire - Siti Rafika Putri; Bambang Budi Rahardjo; Ari Yuniastuti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Perinatal depression affects the health of mothers, children, and families. One approach to preventing postpartum depression is to screen for psychosocial risk factors as early in pregnancy as feasible. The multidimensional Antenatal Risk Questionnaire (ANRQ) was developed to identify psychosocial risk factors during pregnancy. This study undertook the cross-cultural adaptation and initial psychometric testing of the ANRQ among pregnant women in Indonesia. Methods: A methodological study was conducted. A three-round Delphi review involving nine experts was undertaken, together with forward translation, back-translation, and pilot testing. Content validity was assessed using the item-level Content Validity Index (I-CVI) and scale-level Content Validity Index (S-CVI). To assess construct validity, ANRQ scores were compared among women whose risk of depressive symptoms was classified as high risk and low risk using an EPDS-based categorisation method. Cronbach’s alpha was used to assess internal consistency, and the intraclass correlation coefficient (ICC) was used to assess test–retest reliability over a two-week interval. Ninety-three pregnant women were recruited from antenatal care facilities in Bogor Regency, Indonesia, for the initial psychometric evaluation. Results: The Indonesian version of the ANRQ showed preliminary evidence of high content validity in the study population (I-CVI = 0.89–1.00; S-CVI/Ave = 0.983; S-CVI/UA = 0.85). Known-groups validity testing showed significantly higher ANRQ scores among pregnant women classified as being at high risk of depressive symptoms according to EPDS scores than among low-risk participants (p < 0.001). Internal consistency was good (Cronbach’s alpha = 0.85), and test–retest reliability showed good temporal stability (ICC = 0.834, 95% CI: 0.631–0.931; p < 0.001). Conclusion: The Indonesian version of the ANRQ demonstrated preliminary psychometric evidence; however, further validation is required before broader implementation.